Schizogenesis : the art of Rosemarie Trockel - Guinness, Katherine (University of Minnesota Press, 2019)
"Popular and pioneering as a conceptual artist, Rosemarie Trockel has never before been examined at length in a dedicated book. This volume fills that gap, while articulating a new interpretation of feminist theory and bodily identity, based around the idea of schizogenesis central to Trockel's work. Schizogenesis is a fission-like form of asexual reproduction in which new organisms are created but no original is left behind. Author Katherine Guinness applies it in surprising and insightful ways to the career of an artist who has continually reimagined herself and her artistic vision. Drawing on the philosophies of feminists such as Simone de Beauvoir, Shulamith Firestone, and Monique Wittig, Guinness argues that Trockel's varied output of painting, fabric, sculpture, film, and performance is best seen as opening a space that is peculiarly feminist yet not contained by dominant articulations of feminism"--